Can HbA1c detect undiagnosed diabetes in acute medical hospital admissions?. (May 2016) - Manley, Susan E.; O'Brien, Kathleen T.; Quinlan, Diarmuid; Round, Rachel A.; Nightingale, Peter G.; Ali, Fauzi; Durrani, Behram K.; Liew, Aaron; Luzio, Stephen D.; Stratton, Irene M.; Roberts, Graham A.
Abstract : Highlights: HbA1c can identify undiagnosed diabetes in white Caucasian, acute medical hospital admissions. The specificity of HbA1c compared with OGTT for diagnosis of diabetes in acute medical admissions with possible diabetes symptoms/complications is equivalent to patients at risk of diabetes in the community but the sensitivity is lower. The sensitivity of HbA1c for diabetes in hospitalised patients is higher when diagnosed on fasting plasma glucose rather than post glucose load on OGTT. The discrepancy in diagnoses on HbA1c and OGTT may be explained at least in part by transient/stress hyperglycaemia resulting from acute illnesses. Abstract: Objective: To study hyperglycaemia in acute medical admissions to Irish regional hospital. Research design and methods: From 2005 to 2007, 2061 white Caucasians, aged >18 years, were admitted by 1/7 physicians. Those with diabetes symptoms/complications but no previous record of hyperglycaemia ( n = 390), underwent OGTT with concurrent HbA1c in representative subgroup ( n = 148). Comparable data were obtained for 108 primary care patients at risk of diabetes. Results: Diabetes was diagnosed immediately by routine practice in 1% (22/2061) [aged 36 (26–61) years (median IQ range)/55% (12/22) male] with pre-existing diabetes/dysglycaemia present in 19% (390/2061) [69 (58–80) years/60% (235/390) male]. Possible diabetes symptoms/complications were identified in 19% [70 (59–79) years/57% (223/390) male] with their HbA1c similar to primary care patients [54 (46–61) years], 5.7 (5.3–6.0)%/39 (34–42) mmol/mol ( n = 148) vs 5.7 (5.4–6.1)%/39 (36–43) mmol/mol, p = 0.35, but lower than those diagnosed on admission, 10.2 (7.4–13.3)%/88 (57–122) mmol/mol, p < 0.001. Their fasting plasma glucose (FPG) was similar to primary care patients, 5.2 (4.8–5.7) vs 5.2 (4.8–5.9) mmol/L, p = 0.65, but 2hPG higher, 9.0 (7.3–11.4) vs 5.5 (4.4–7.5), p < 0.001. HbA1c identified diabetes in 10% (15/148) with 14 confirmed on OGTT but overall 32% (48/148) were in diabetic range on OGTT. The specificity of HbA1c in 2061 admissions was similar to primary care, 99% vs 96%, p = 0.20, but sensitivity lower, 38% vs 93%, p < 0.001 (63% on FPG/23% on 2hPG, p = 0.037, in those with possible symptoms/complications). Conclusion: HbA1c can play a diagnostic role in acute medicine as it diagnosed another 2% of admissions with diabetes but the discrepancy in sensitivity shows that it does not reflect transient/acute hyperglycaemia resulting from the acute medical event.